2017
DOI: 10.1159/000485662
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Resting Metabolic Rate May Modify through Expression of Vitamin D Receptor and Peroxisome Proliferator-Activated Receptor Gamma Coactivator-1 Alpha Gene in Overweight and Obese Adults

Abstract: Background: Resting metabolic rate (RMR) used to prognosticate and measure the amount of energy required. Vitamin D is known as a new predictor of RMR. The aim of this study is to investigate the relationship between vitamin D effects on RMR in connection with the vitamin D receptor (VDR) and peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) gene expression. Methods: We enrolled 298 overweight and obese adults in this cross-sectional study. Body mass index (BMI), fat mass, fat-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The driver for our study was observations that vitamin D status had a direct association with RMR in Australian adults after accounting for several confounding factors (Calton et al, 2016). This has also been observed in a large number of Iranian overweight and obese where a significant positive correlation between vitamin D status and RMR/kg was obtained (Sajjadi et al, 2018). However, a short-term (7 days) randomized controlled trial of vitamin D supplementation (2000 IU), which was conducted on 10 young men, did not show any effect of vitamin D on energy expenditure (Boon et al, 2006).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The driver for our study was observations that vitamin D status had a direct association with RMR in Australian adults after accounting for several confounding factors (Calton et al, 2016). This has also been observed in a large number of Iranian overweight and obese where a significant positive correlation between vitamin D status and RMR/kg was obtained (Sajjadi et al, 2018). However, a short-term (7 days) randomized controlled trial of vitamin D supplementation (2000 IU), which was conducted on 10 young men, did not show any effect of vitamin D on energy expenditure (Boon et al, 2006).…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, higher prevalent vitamin D status was associated with greater postprandial thermogenesis and insulin sensitivity (Pathak et al, 2017). A study published in Iran also reported the role of VDR in the regulation of RMR (Sajjadi, Mirzaei, Khorrami-Nezhad, Maghbooli, & Keshavarz, 2018). Therefore, this study aimed to determine the association of vitamin D status with RMR independent of body composition in Tehranese adults.…”
Section: Introductionmentioning
confidence: 94%
“…In diabetic animal models, vitamin D increases irisin expression [160]. In overweight and obese patients, depletion of vitamin D is associated with worsened inflammatory state in obese [161], whereas vitamin D stimulus upregulated PGC-1α expression and consequently irisin secretion [162] Moreover, Safarpour et al have demonstrated that in obese and diabetic subjects vitamin D supplementation counteracts impaired insulin signaling and increased irisin signaling pathway [163]. Then, the relationship between irisin and vitamin D should be further investigated.…”
Section: Irisin: Nutritional Interventionsmentioning
confidence: 99%
“…Notwithstanding, this effect may, at least in part, be due to dietary calcium-induced increased D r a f t fecal fat excretion (Christensen et al 2009;Kjølbaek and Lorenzen 2017). On the other hand, the effect of vitamin D on RMR and body weight may be mediated through VDR (Sajjadi et al 2018). Adequate intake of dairy calcium and vitamin D may help weight loss (Shahar et al 2010) probably through, at least in part, increased EE.…”
Section: R a F Tmentioning
confidence: 99%